Identifying Potential Plasmodium vivax Sporozoite Stage Vaccine Candidates: An Analysis of Genetic Diversity and Natural Selection - Garzón-Ospina, Diego; Buitrago, Sindy P.; Ramos, Andrea E.; Patarroyo, Manuel A. (Frontiers in Genetics, 2018)
Parasite antigen genetic diversity represents a great obstacle when designing a vaccine against malaria caused by Plasmodium vivax. Selecting vaccine candidate antigens has been focused on those fulfilling a role in invasion and which are conserved, thus avoiding specific-allele immune responses. Most antigens described to date belong to the blood stage, thereby blocking parasite development within red blood cells, whilst studying antigens from other stages has been quite restricted. Antigens from different parasite stages are required for developing a completely effective vaccine; thus, pre-erythrocyte stage antigens able to block the first line of infection becoming established should also be taken into account. However, few antigens from this stage have been studied to date. Several P. falciparum sporozoite antigens are involved in invasion. Since 77% of genes are orthologous amongst Plasmodium parasites, P. vivax sporozoite antigen orthologues to those of P. falciparum might be present in its genome. Although these genes might have high genetic diversity, conserved functionally-relevant regions (ideal for vaccine development) could be predicted by comparing genetic diversity patterns and evolutionary rates. This study was thus aimed at searching for putative P. vivax sporozoite genes so as to analyse their genetic diversity for determining their potential as vaccine candidates. Several DNA sequence polymorphism estimators were computed at each locus. The evolutionary force (drift, selection and recombination) drawing the genetic diversity pattern observed was also determined by using tests based on polymorphism frequency spectrum as well as the type of intra- and inter-species substitutions. Likewise, recombination was assessed both indirectly and directly. The results showed that sporozoite genes were more conserved than merozoite genes evaluated to date. Putative domains implied in cell traversal, gliding motility and hepatocyte interaction had a negative selection signal, being conserved amongst different species in the genus. PvP52, PvP36, PvSPATR, PvPLP1, PvMCP1, PvTLP, PvCelTOS and PvMB2 antigens or functionally restricted regions within them would thus seem promising vaccine candidates and could be used when designing a pre-erythrocyte and/or multi-stage vaccine against P. vivax to avoid allele-specific immune responses that could reduce vaccine efficacy.